The risk factors of measles outbreak in Dollo zone Somali region, Ethiopia - Ali, Abdisalan M.; Maalin, Mohammed A. (International Journal Of Community Medicine And Public Health, 2021)
Background: Measles is a highly contagious acute viral illness with the possibility of severe and dangerous complications. Measles occurrence is related to urbanization because of high entry of migrants and high population density; cities have become important hubs for the spread of infectious diseases. The African region is a crucial player in the global fight against measles and has made tremendous progress in its effort to immunize children and to control the disease. Despite the accessibility of safe and cost-effective vaccine, measles has remained endemic with persistent periodic outbreaks in the horn of Africa. Methods: We reviewed the measles cases line lists in Dollo zone from January 2017 to March 2018. There was a total of 771-line listed cases in 2017 and 326 line-listed in 2018. Measles case investigations on alerts were also reviewed when there is an alert rumors verification case investigation done. The line list included variables on vaccination status, age, sex, treatment modality, date of onset the rash, date seen health facility, diagnosis, outcome (alive or dead), locations from place cases came from, contact history and travel history were reviewed. Results: We found that the measles outbreak affected different age groups in Dollo zone and most affected age group were between the ages of 15 years to 30 years and most of the cases have no history of immunization. Conclusions: The outbreak affected all age groups, which may show the continuous low routine immunization coverage over several years and the gathering of the susceptible population in the older age group that may have led to the current outbreak.